Item analysis of Objective Structured Clinical Examination (OSCE) assessment rubrics for undergraduate pharmacy students - Mohamed Nazar, Nor Ilyani; Ab Rahman, Norny Syafinaz; Zin, Che Suraya (2019)
Introduction: Objective Structured Clinical Examination (OSCE) is one of the assessments that objectively evaluate the students' competency in handling the specific hands-on clinical tasks. The rubrics of the assessment is very critical to be evaluated ensuring its validity. Objectives: This study aimed to evaluate the usefulness of the item analysis method in objectively analyse the validity of the assessment rubrics developed for OSCE in the field of pharmacy. Methodology: Fifty-four (54) students participated in the OSCE and were divided into three groups of the concurrent session with four active stations and two preparatory stations. The examiners were well-trained on the assessment rubrics before the examination for standardization. The questions and assessment rubrics were developed and vetted earlier in a group of vetting committee who were expert in the field of pharmacy practice and languages. There were four (4) tasks in the active stations namely; i) Insulin device counselling, ii) Extemporaneous preparation of spironolactone syrup, iii) Unit of dose supply and iv) Psychotropic drugs recording and supply. Results: Majority of the items in the rubrics showed acceptable levels of discrimination (>0.3) and difficulty (0.25-0.85) index except for a few items that need to be reviewed and improvised literally or constructively. Conclusion: Item analysis method is useful in analysing the validity of the assessment rubrics developed for OSCE in Pharmacy field.